Learning digital skills online: empowering older adults through one-to-one, online digital training provision - Wilson-Menzfeld, Gemma; Gates, Jessica Raven; Moreland, Mary; Raw, Helen; Johnson, Amy (Frontiers in Psychology, 2023)
Digital exclusion, through lack of access and poor digital skills can have a significant adverse impact on daily living. The COVID-19 pandemic not only had a dramatic impact on the necessity of technology in our daily lives, but also on the availability of digital skills programmes. This study aimed to explore perceived facilitators and barriers of a digital skills programme that was delivered remotely, online and to reflect on this form of training as a possible alternative to traditional face-to-face models. Individual interviews were carried out with programme participants, and the programme instructor. and two themes were generated from this data: (a) Creating a unique learning environment; and (b) Encouraging further learning. Barriers to digital delivery were evident within this programme, however, the individual and personalised delivery empowered participants within their own learning, supporting individuals to learn skills relevant to them and to continue their digital learning journey.